Prospective Evaluation of the Clinical Utility of the International Lung Screen Trial Lung Nodule Management Protocol - Lam, S.; Myers, R.; Atkar-Khattra, S.; Yuan, R.; Yee, J.; English, J.; Grant, K.; Lee, A.; Mcguire, A.; McWilliams, A.; Brims, Fraser; Stone, E.; et al. (ELSEVIER SCIENCE INC, 2018)
No Abstract Available